Penguatan Filantropi Islam pada Santri dengan Kupon Shadaqah dan Wakaf - Rif’ah, Sifwatir; Muawanah , Rifatul (Al-Musthofa: Journal of Sharia Economics, 2025)
The purpose of this study was to examine the role of sedekah and waqf coupons as a medium for strengthening Islamic philanthropy for students. The method that the author uses in this study is a qualitative descriptive method using SWOT analysis. The results of this study are sedekah and waqf coupons are able to increase Islamic philanthropy in the students so as to create prosperity in life and be able to help improve the development of the Islamic economy.